PENDIDIKAN PRANIKAH TERHADAP KESIAPAN MENGHADAPI KEHAMILAN PERTAMA PADA CALON PENGANTIN PUTRI - Dewi Rokhanawati; Umu Hani Edi Nawangsih (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: Pregnancy is the first phase of the reproductive cycle that needs to be prepared by the bride. At the time of pregnancy occurs share the changes that will affect the physical and psychological condition of women. Objective: to determine the effect of premarital education preparedness first pregnancy at bride in KUA Region Bantul, Yogyakarta in 2014. Methods: Data were collected through questionnaires pre and posttest to 43 bride chosen by accidental in September 2014. Analysis data by paired t test. Results: show after educational intervention premarital decrease of respondents who are not ready to face the first pregnancy of 57.5% down to 39.5%. Premarital education affect the first pregnancy preparedness on the bride at KUA Bantul district of Yogyakarta in 2014 (p value = 0.000). Suggestion: to KUA Bantul district is expected to cooperate with the local health center to revive the course program bride. Keywords: predisposing factors, the level of premarital sexual behavior